1995
DOI: 10.1128/mcb.15.8.4215
|View full text |Cite|
|
Sign up to set email alerts
|

Cellular Targets for Activation by the E2F1 Transcription Factor Include DNA Synthesis- and G1/S-Regulatory Genes

Abstract: Although a number of transfection experiments have suggested potential targets for the action of the E2F1 transcription factor, as is the case for many transcriptional regulatory proteins, the actual targets in their normal chromosomal environment have not been demonstrated. We have made use of a recombinant adenovirus containing the E2F1 cDNA to infect quiescent cells and then measure the activation of endogenous cellular genes as a consequence of E2F1 production. We find that many of the genes encoding S-pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
653
2
2

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 855 publications
(687 citation statements)
references
References 70 publications
30
653
2
2
Order By: Relevance
“…As shown in Figure 1b, ChIP analysis revealed that Myc bound to the E2F1, E2F2 and E2F3 promoters as early as 4 h following serum stimulation and persisted on these promoters through S phase (16 h). E2F1 protein was detected on the E2F1, E2F2 and E2F3 promoters at 12 and 16 h following serum stimulation, times corresponding to the previously documented initiation of E2F mRNA and protein accumulation (DeGregori et al, 1995;Leone et al, 1998). Examination of the levels of Myc and E2F1 in these nuclear fractions by western blot revealed that the patterns of Myc and E2F1 binding to E2F promoters coincided with the kinetics of protein accumulation for both proteins (Figure 1c).…”
Section: Resultssupporting
confidence: 71%
“…As shown in Figure 1b, ChIP analysis revealed that Myc bound to the E2F1, E2F2 and E2F3 promoters as early as 4 h following serum stimulation and persisted on these promoters through S phase (16 h). E2F1 protein was detected on the E2F1, E2F2 and E2F3 promoters at 12 and 16 h following serum stimulation, times corresponding to the previously documented initiation of E2F mRNA and protein accumulation (DeGregori et al, 1995;Leone et al, 1998). Examination of the levels of Myc and E2F1 in these nuclear fractions by western blot revealed that the patterns of Myc and E2F1 binding to E2F promoters coincided with the kinetics of protein accumulation for both proteins (Figure 1c).…”
Section: Resultssupporting
confidence: 71%
“…Previous reports using mouse and rat embryonic fibroblasts showed that ectopic expression of E2F1 and E2F2 leads to an increase in TS transcripts (DeGregori et al, 1995;Ishida et al, 2001). To further characterise the relationship between key effectors of G 1 /S transition and the regulation of human TS transcription, we infected HCT116 and MCF-7 cells with recombinant adenoviruses expressing E2F1, Dp1 and cyclin E. Western blot analysis revealed that, 24 h post-infection, both cyclin E and E2F1 were over-expressed in both cell lines ( Figure 4A and C).…”
Section: Kinetics Of Expression Of Cyclin E and Thymidylate Synthase mentioning
confidence: 95%
“…As G 1 progresses, pRb is phosphorylated by these complexes (Weinberg, 1995;Blagosklonny and Pardee, 2002), ultimately leading to E2F release. E2F transcription factors play an essential role in cell-cycle progression and are directly involved in the regulation of genes required for the G 1 /S transition as well as genes related to DNA synthesis (DeGregori et al, 1995). E2F can bind DNA as a homodimers or heterodimer containing the co-activator Dp1 to activate the transcription of target genes such as cyclin E. Newly synthesised cyclin E then forms a complex with CDK2 to drive Sphase entry (Sauer and Lehner, 1995;Woo and Poon, 2003).…”
mentioning
confidence: 99%
“…Interestingly, the expression of E2F1-3 and cyclin A are precisely regulated during the cell cycle (reviewed in Loughan and La Thangue 6 ). The levels of E2F are high at the G 1 /S transition, 14,15 whereas cyclin A is high at mid-S to G 2 /M. 16 As cyclin A competes with p53 for binding to E2F1-3, 8 E2F has a window of opportunity to regulate p53 at the G 1 /S transition when E2F1-3 levels are high and the cyclin A and Ser315-phosphorylated p53 are relatively low.…”
Section: The E2f Familymentioning
confidence: 99%